Parental Sexual Education Style and its Impact on Religious Attitude: The Mediating Role of Islamic Spiritual Health - Rajabi, Fahimeh; Salmanpour, Sadegheh; Bayramnejad, Horeye; Doodman, Parvaneh (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: Sexual education presents a series of essential psychological, physical, and religious information in the domain of individual sexual aspects along with providing individuals with knowledge and awareness in understanding the characteristics of the opposite gender. The current study aimed to present a structural model of sexual education style with the mediating role of spiritual health on the religious attitudes of high school students in Shiraz. Materials and Methods: This descriptive-correlational research included all female high school students in Shiraz during the academic year 2023-2024 and their parents, with a total of 1234 students selected through cluster random sampling method according to the Morgan formula. Data collection tools included the Surajzadeh Religious Attitude Questionnaire, the Islamic Spiritual Health Questionnaire by Miri et al. (2016), and the Abdollahzadeh and Keykhosravi Sexual Education Style Questionnaire. Data were analyzed using Amos software. Findings: The findings indicated that the permissive sexual education style has a direct negative effect on spiritual health. Furthermore, the relationship between this style and religious attitude is negatively significant considering the mediating role of spiritual health. Additionally, the authoritative style has a direct and significant effect on spiritual health, and the relationship between this style and religious attitude is positively significant considering the mediating role of spiritual health. The authoritarian style has no direct or indirect relationship with spiritual health and religious attitude. Also, spiritual health has a direct and significant effect on religious attitude. Conclusion: In conclusion, sexual education plays a pivotal role in imparting psychological, physical, and religious knowledge. The study elucidated a structural model of sexual education, revealing the permissive style’s detrimental impact on spiritual health, while the authoritative style positively influenced both spiritual health and religious attitudes among high school students in Shiraz.